2016
DOI: 10.17957/ijab/15.0195
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of Drought Stress Adverse Effect and Mediating Biochemical Content of Cabbage Seedlings by Plant Growth Promoting Rhizobacteria

Abstract: To cite this paper: Samancioglu, A., E. Yildirim, M. Turan, R. Kotan, U. Sahin and R. Kul, 2016 AbstractThe goals of the study were to investigate the role of plant growth promoting rhizobacteria (PGPR) (Bacillus megaterium TV-6D, Bacillus megaterium TV-20E, Peanibacillus polymyxa KIN-37, and combination of Bacillus megaterium TV-6D +Pantoea agglomerans RK-92+Brevibacillus choshiensis TV-53D) in alleviating the harmfull effects of drought stress in cabbage seedlings grown under different irrigation levels. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 36 publications
0
5
0
1
Order By: Relevance
“…As per the findings of Marulanda et al [37], these microbial treatments may also help to enhance the levels of IAA growth regulators, which also contribute to improvised seedling growth parameters, including root and shoot fresh weight and leaf area [38]. Further, the infusion of vermicompost with T. harzianum in cabbage greatly enhanced the seedling's establishment rate [39].…”
Section: Discussionmentioning
confidence: 75%
“…As per the findings of Marulanda et al [37], these microbial treatments may also help to enhance the levels of IAA growth regulators, which also contribute to improvised seedling growth parameters, including root and shoot fresh weight and leaf area [38]. Further, the infusion of vermicompost with T. harzianum in cabbage greatly enhanced the seedling's establishment rate [39].…”
Section: Discussionmentioning
confidence: 75%
“…Conversely, ABA content was elevated by increased NaCl concentration. Similarly, it has been also reported that the amount of ABA increased in plants grown under abiotic stress conditions, but the amount of IAA and GA decreased (Samancioglu et al 2016). It has been understood that IAA shows a response mechanism in agricultural plants under salt stress.…”
Section: H2smentioning
confidence: 78%
“…The strain ATMLC22021 was grouped within the clade of B. megaterium . This species has extensively been studied [ 31 , 32 , 33 , 34 , 35 ]. In genome analysis, it was reported to possess multiple genes that contribute to plant growth under drought conditions, such as genes related to IAA synthesis, P-solubilization, siderophore and volatile organic compound production, and the synthesis of osmoprotectants such as trehalose, glycine/betaine, and spermidine.…”
Section: Discussionmentioning
confidence: 99%